2018
DOI: 10.14254/2071-8330.2018/11-2/14
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of theory of constraint in predicting Ghanaian SMEs investment decisions

Abstract: Abstract. This study investigated dimensions of SME's constraints and decisions to Invest in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…As previously reported (Soderlund & Ohman, 2003;Clark-Murphy & Soutar, 2008;K. M. Appiah et al, 2018a;Appiah et al, 2018bAppiah et al, , 2018cMK. Appiah et al, 2021) investment intentions of firms are severally determined.…”
Section: Investment Intentionsupporting
confidence: 82%
See 1 more Smart Citation
“…As previously reported (Soderlund & Ohman, 2003;Clark-Murphy & Soutar, 2008;K. M. Appiah et al, 2018a;Appiah et al, 2018bAppiah et al, , 2018cMK. Appiah et al, 2021) investment intentions of firms are severally determined.…”
Section: Investment Intentionsupporting
confidence: 82%
“…Appiah et al, 2021) Ghana being a low middle income country has huge potentials to transform and grow its economy through industrialization, innovation, job creation and ultimately ensuring equitable distribution of wealth. The 2013 local content regulation was formulated with the fundamental aim of optimizing locally produced materials, personnel, goods and services as well as financing, which are enshrined in the petroleum industry value chain and can best be measured in monetary terms (K. M. Appiah et al, 2018a;Appiah et al, 2018b). The petroleum sub sector policy directions are intended to guide the development and management of the emerging oil and gas sector as enabler of oil and gas sector for socio-economic transformation.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it should be stressed that the company's internal potential is most strongly influenced by the potential and commitment of its employees that can be directly influenced by the individual activities of human resources management (Stachová et al, 2019). This is becoming even more critical in small and medium enterprises (SMEs) as they play a vital role in job creation (Koisova et al, 2017;Appiah et al, 2018) and are recognized as one of the main contributors to economic, development and employment growth (Cepel et al, 2018;Kljucnikov et al, 2016;Mura, 2019). Extensive and unregulated use of cybervetting by SMEs can reduce their credibility in potential employees' eyes, which could have, given the important position of SMEs, enormous consequences even though the Czech and Slovak economy still focuses on cheap labour which is not so sensitive about privacy.…”
Section: Discussionmentioning
confidence: 99%
“…Avalanches of previous studies (Kazimoto, 2014;Farsi & Toghraee, 2014;Bouazza, Ardjouman & Abada, 2015) reported mixed results between SMEs internal characteristics and investment decisions. Although whopping majority of the previous studies (Bouazza, Ardjouman & Abada, 2015;Quartey, Turkson, Abor & Iddrisu, 2017;Appiah, Possumah, Ahmat, & Sanusi, 2018a, 2018b reported positive and significant association between internal firm factors and investment decisions, negative and insignificant results had also been moderately reported (Khaled, 2012;Ayyagari, Demirgüç-Kunt & Maksimovic, 2011;. The reasons accounting for variations in the previous results can be attributed to: (1) different methods, different SMEs internal variables and different measures of investment decisions used in them.…”
Section: Introductionmentioning
confidence: 91%